1994
DOI: 10.1002/jcc.540150608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of charge on bond strength in hydrogenated amorphous silicon

Abstract: We have studied the effect of excess charge on the bond strength in the silanes SiH4 and Si2H6 to assess whether charge trapping in a solid-state lattice might promote the technologically important photodegradation of amorphous silicon alloys (the Staebler-Wronski effect). The calculations indicate that both positive and negative charges reduce the strength of Si-H and Si-Si bonds considerably, to the point where they may be broken easily by visible or even infrared light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Combined density functional/molecular dynamics calculations have been used recently to show pressureinduced amorphization in a Si 35 H 36 cluster. 24 In earlier work, 25 the Murdoch group estimated the energies required to break Si-H bonds in molecules related to the silanes SiH 4 and Si 2 H 6 using Hartree-Fock calculations with and without estimates of the correlation energy obtained from second-order Mo "ller-Plesset perturbation theory ͑MP2͒. These calculations suggested that both positive and negative charges reduce the strength of Si-H and Si-Si bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Combined density functional/molecular dynamics calculations have been used recently to show pressureinduced amorphization in a Si 35 H 36 cluster. 24 In earlier work, 25 the Murdoch group estimated the energies required to break Si-H bonds in molecules related to the silanes SiH 4 and Si 2 H 6 using Hartree-Fock calculations with and without estimates of the correlation energy obtained from second-order Mo "ller-Plesset perturbation theory ͑MP2͒. These calculations suggested that both positive and negative charges reduce the strength of Si-H and Si-Si bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang [7] suggested that the charge weakens the bond strength and as a result the CNPs could have a liquid-like property. Weakening the bond strength of Si-H and Si-Si by the charge was confirmed using ab-initio calculations in SiH4 and Si2H6 by Clare et al [9]. For a singly-charged nanoparticle, this effect of weakening the bond strength would decrease with increasing the size of CNPs.…”
Section: Introductionmentioning
confidence: 73%
“…Therefore, the most important assumption of the TCN that CNPs are liquid-like would be related to the weakening of the bond strength by charge. Clare et al (1994) published ab initio calculations most relevant to this assumption. Clare et al (1994) studied the effect of charge on bond strength in hydrogenated amorphous silicon to assess whether charge trapping in a solid-state lattice might promote the photo-degradation of amorphous silicon alloys (the Staebler-Wronski effect).…”
Section: Theory Of Charged Nanoparticlesmentioning
confidence: 96%
“…Clare et al (1994) published ab initio calculations most relevant to this assumption. Clare et al (1994) studied the effect of charge on bond strength in hydrogenated amorphous silicon to assess whether charge trapping in a solid-state lattice might promote the photo-degradation of amorphous silicon alloys (the Staebler-Wronski effect). They did ab initio calculations of the effect of a single negative or positive charge on the strength of a silicon-silicon and silicon-hydrogen bond in the molecules SiH 4 and Si 2 H 6 .…”
Section: Theory Of Charged Nanoparticlesmentioning
confidence: 96%